Is Water-Only Fasting Safe? - Ewa Ogłodek MD, PhD; Wiesław Pilis, Prof (SAGE Publishing, 2021)
Background Water-only fasting (WF) is a practice used to improve and maintain health. Objective The aim of the study was to show whether WF performed for 8 days may be a threat to the health and/or life of people undergoing this practice. Methods Twelve middle-aged men participated in the study. During the 8-day WF, the subjects ate no food except for drinking mineral water. Before and after WF, all subjects had a series of tests performed, beginning with the level of perceived stress and somatic measurements. The concentrations of creatinine, sodium (Na + ), potassium (K + ), total calcium (Ca), magnesium (Mg ++ ), urea (U), uric acid (UA) and total protein were determined in this urine and in the serum. For these substances, the values ​​of clearance, renal filtration and fractional excretion were calculated. The osmotic clearance and free water clearance as well as the amount of daily urinary excretion of creatinine, Na + , K + , Ca, Mg ++ , U and UA were also calculated. Moreover, the concentration of glucose in the serum and the concentration of β-hydroxybutyrate in the plasma were determined. In urine, specific gravity, pH and osmolality were also measured. Results After 8 days of WF, the study showed a significant reduction in the level of perceived stress, weight loss, changes in body composition, dehydration, increased ketogenesis, hyperuricemia, decreased serum glucose concentration, and hyponatremia. These changes were accompanied by Na + , K + and protein sparing, decreased serum Ca and Mg ++ concentrations, and reduced daily volume of more acidic urine with elevated specific gravity. Conclusions After 8 days of WF, all subjects were found to remain safe and feel the sense of well-being. However, the appearance of the above-mentioned adverse metabolic effects, despite partially effective renal compensations, suggests that the further continuation of fasting intervention by the subjects would be detrimental to their body.